Disproportionate minority contact among juveniles adjudicated for sexual, violent, and general offending: the importance of home, school, and community contexts - Fix, Rebecca L. (Crime & delinquency, 2017)
The present study tested whether differences in violence exposure and parent and peer attachment help explain why disproportionate minority contact is lower among adolescents adjudicated for sexual offending than among adolescents adjudicated for other offenses. The 1,109 male juvenile offenders recruited from a juvenile detention center were interviewed, completed self-report measures, and legal documentation of prior offenses was obtained. Using a hierarchical multinomial logistic regression, a unique constellation of factors were found to predict sexual and violent offending relative to general offending. Moreover, the influence of race/ethnicity was diminished in the final model, suggesting disproportionate minority contact is partially explained by contextual factors.